Generalized Anxiety and C-Reactive Protein Levels: A Prospective, Longitudinal Analysis - Copeland, William E. (2012)
BACKGROUND: Generalized Anxiety Disorder (GAD) is highly comorbid with depression. Depression is associated with elevated levels of the inflammation marker C-reactive protein (CRP), cross-sectionally and over time. To date, no studies have looked at the association of CRP with GAD. METHODS: Ten waves of data from the prospective population-based Great Smoky Mountains Study (N = 1,420) were used, covering children in the community aged 9-16, 19, and 21 years old. Structured interviews were used at each assessment to assess GAD symptoms, diagnosis, and cumulative episodes. Bloodspots were collected and assayed for CRP levels. RESULTS: GAD was associated with increased levels of CRP in bivariate cross-sectional analyses. These bivariate associations, however, were attenuated after accounting for demographic, substance use, and health-related covariates. In longitudinal models, there was little evidence that CRP predicted later GAD. Associations from GAD to later CRP were attenuated in models adjusted for health-related coavariates and there was evidence that the GAD-CRP association was mediated by BMI and medication use. CONCLUSIONS: Similar to depression, GAD was associated with elevated levels of CRP, but the effect of GAD on CRP levels was explained by the effect of GAD on health-related behaviors such as BMI and medication use. This study suggests differences in the association between inflammation and depression and GAD.